Dual-targeting of EGFR and Neuropilin-1 attenuates resistance to EGFR-targeted antibody therapy in KRAS-mutant non-small cell lung cancer - Kim, Ye Jin; Baek, Du San; Lee, Seyoung; Park, Daechan; Kang, Han Na; Cho, Byoung Chul; Kim, Yong Sung (Cancer Letters, 2019)
The therapeutic targeting of oncogenic KRAS mutant-harboring (KRASMUT) non-small cell lung cancer (NSCLC) is an urgent unmet need in cancer therapy. Although NSCLC is often driven by epidermal growth factor receptor (EGFR) overexpression and/or mutations, no EGFR-targeted therapy is clinically available for KRASMUT NSCLC. In this study, we show that integrin β3 expression is associated with the intrinsic resistance of KRASMUT NSCLCs to the anti-EGFR antibody cetuximab. Further analyses identified an integrin β3-mediated ternary complex comprising NRP1–integrin β3–KRASMUT and its downstream signaling of PI3K-Akt and RalB-TBK1 as a primary resistance mechanism of KRASMUT NSCLC to cetuximab treatment. Importantly, we demonstrate that the EGFR/NRP1 dual-targeting bispecific antibody, Ctx-TPP11, attenuates the downstream signaling driven by the ternary complex via the cellular co-internalization and degradation of the NRP1-coupled complex, resulting in the alleviation of cetuximab resistance in KRASMUT NSCLCs in vitro and in vivo, including patient-derived xenograft mouse models. Our study shows that the dual-targeting of EGFR and NRP1 with a bispecific antibody might be an effective therapeutic strategy for KRASMUT NSCLC.
Keywords: Bispecific antibody; Cetuximab resistance; EGFR/NRP1 dual-targeting; Integrin β3; KRAS mutation